Education, Knowledge, Attitude, and Balanced Diet Practices Among Adult Women in Banten, Indonesia - Patricia Budihartanti Liman; Nugroho Abikusno (Jurnal Biomedika dan Kesehatan, 2022)
Background The prevalence of diabetes mellitus is increasing in Indonesia and the known contributing factors are age, physical activity, smoking, and diet. Education plays a role in increasing knowledge, and might influence one's attitudes and practices. Studies on the role of knowledge, attitude and balanced diet practices are scarce in Indonesia and still remain controversial. The aim of the study was to determine the relationship between education and knowledge and their effects on attitude and balanced diet practices. Method This was a cross sectional study that involved 56 women aged 18 years and above. Questionnaires and modified structured questionnaires were used to assess sociodemographic factors, knowledge, attitudes, and practice. Scores of education, knowledge, attitude, and practice were categorized as low and sufficient. Data were analyzed using SPSS ver.28.0.1.1. Simple and multivariate logistic regression were used to assess the relationship between sufficient scores and sociodemographic factors: age, education, working status, income, and disease history. Results Median age of women in our study was 43 years old with 33.9% of them had minimal education level of graduated Diploma. Around 28.6% and 17.1% of subjects had low knowledge and attitude, respectively, and 81.4% had poor balanced diet practices. Education was positively associated with knowledge levels (adjusted OR = 5.35 [95%CI: 1.05, 27.25], p=0.04). However, knowledge was not found associated with attitude ((OR = 2.16 [95%CI: 0.24, 19.38], p=0.49) and attitude was not found associated with balanced diet practices, even after the adjustment with covariates (adjusted OR = 2.27 [95%CI: 0.25, 20.84], p=0.469). Conclusion Our study showed that the level of education was positively associated with knowledge but we have not found association between knowledge and attitude and between attitudes and balanced diet practice. A program needs to be designed to increase attitude and balanced diet practices, that can be used to control the development of diabetes in this population.